The Effectiveness of Experiential Learning in Teaching Arithmetic and Geometry in Sixth Grade - Uyen, Bui Phuong; Tong, Duong Huu; Lien, Nguyen Bich (Frontiers in Education, 2022)
Many educators and policymakers worldwide have noticed the burgeoning field of experiential learning in the twenty-first century. Learning theory and practice together is beneficial to education in general, and mathematics education in particular, because it enables students to realize their full potential for knowledge and skill, and it connects the two aspects of knowledge. A focus on the cross-cutting and critical role of experience activities within the framework was emphasized in Vietnam’s general education program in mathematics, released in 2018 and included views on the content and methods of teaching and learning mathematics in the country. Experiential learning in mathematics was studied to see if this method could positively help students participate, increase their motivation and interest in learning, and impact their math outcomes. A series of pedagogical experiments with 29 sixth-grade students on arithmetic and geometric topics was conducted to confirm the research goals. Students were required to develop solutions to real-world problems related to their studying subjects. The experimental and control classes are subjected to a pre-test and a post-test design. Mixed methods, including qualitative and quantitative analysis, are handled by the statistical data processing software (SPSS) program and the results of observations and surveys of learners’ opinions. The results were found that experiential learning activities positively influenced math learning attitudes and student achievement progress in the classroom.